Frequency and Boolean Based Secret Shared Watermarking for Authentication of Video Data - Latha, Bhargavi; Reddy, D. Venkat; Chythanya, N. Krishna (European Journal of Applied Sciences, 2017)
Video watermarking refers to the process of embedding authentic patenting information in to bit streams of videos. The authentication of the digital data has become the need of the hour in this digital era. This paper emphasizes the combined use of frequency domain and Boolean based secret sharing scheme for generating an authentication using watermarked video frames.